Food and social security at the margins - The Parhaiyas of Jharkhand - Somanchi, Anmol (Economic and Political Weekly)
A survey of all particularly vulnerable tribal group households in two blocks of Jharkhand reveals that their lives remain precarious due to disrupted livelihoods, limited access to education and other public services, and continued exploitation. The public distribution system has become a crucial source of support for them: most such households have ration cards and receive the bulk of their monthly food rations. Social security pensions also help, but exclusion rates are higher, and they have recently been disrupted by Aadhaar-related problems, as have a range of other schemes. Yet, despite these useful social security measures, food insecurity remains common among PVTGs. - Reproduced
Keywords: Tribal development, Parhaiyas tribes, Food security, Social security, Margins, Jharkhand